Low levels of hepatitis C diagnosis and testing uptake among people who inject image and performance enhancing drugs in England and Wales, 2012-15. (1st October 2017) - Hope, V.D.; McVeigh, J.; Smith, J.; Glass, R.; Njoroge, J.; Tanner, C.; Parry, J.V.; Ncube, F.; Desai, M.
Highlights: One in 20 people who inject image & performance enhancing drugs (IPEDs) have hepatitis C antibodies. Uptake of hepatitis C testing was poor; less than two-fifths had ever been tested. Among those only injecting IPEDs, most were not aware of having hepatitis C antibodies. Abstract: Introduction: People injecting image and performance enhancing drugs (IPEDs) have traditionally not been perceived as being at high risk of hepatitis C virus (HCV) infection. However, recent studies indicate the HCV antibody (anti-HCV) prevalence in this group is 10-times that in the general population. HCV testing uptake and undiagnosed infections are examined using data from a voluntary unlinked-anonymous survey. Method: People injecting IPEDs across England and Wales completed a short bio-behavioural survey (2012–15). Anti-HCV status and self-reports of HCV testing were used in the analysis. Results: The participants median age was 31 years, 98% were men, 14% had also injected psychoactive drugs and the anti-HCV prevalence was 4.8% (N = 564). Among those who had never injected psychoactive drugs the anti-HCV prevalence was 1.4%; among those who had recently injected psychoactive drugs (preceding 12 months) prevalence was 39% and among those who had done this previously 14% (p < 0.001). Overall, 37% had been tested for HCV: among those who had recently injected psychoactive drugs 78% had been tested, as had 56% of those who had injected psychoactive drugs previously; 33% of those never injecting psychoactive drugs were tested (p < 0.001). Overall, 44% of those with anti-HCV were aware of this; however, only 14% of those who had never injected psychoactive drugs were aware. Conclusions: One-in-twenty people who inject IPEDs have anti-HCV. HCV infections among those who had never injected psychoactive drugs were mostly undiagnosed, though this group had a lower prevalence. Targeted HCV testing interventions are also needed for those injecting IPEDs.